Quality of life among tuberculosis (TB), TB retreatment and/or TB-HIV co-infected primary public health care patients in three districts in South Africa - Louw, Julia (BioMed Central, 2012)
INTRODUCTION: TB and HIV co-morbidity amount to a massive burden on healthcare systems in many countries. This study investigates health related quality of life among tuberculosis (TB), TB retreatment and TB-HIV co-infected public primary health care patients in three districts in South Africa. METHODS: A cross sectional study was conducted among 4900 TB patients who were in the first month of anti-TB treatment in primary public health care clinics in three districts in South Africa. Quality of life was assessed using the social functioning (SF)-12 Health Survey through face to face interviews. Associations of physical health (Physical health Component Summary = PCS) and mental health (Mental health Component Summary = MCS) were identified using logistic regression analyses. RESULTS: The overall physical and mental health scores were 42.5 and 40.7, respectively. Emotional role, general health and bodily pain had the lowest sub-scale scores, while energy and fatigue and mental health had the highest domain scores. Independent Kruskal–Wallis tests found significant positive effects of being TB-HIV co-infected on the domains of mental health functioning, emotional role, energy and fatigue, social function and physical role, while significant negative effects were observed on general health, bodily pain and physical function. In multivariable analysis higher educational, lower psychological distress, having fewer chronic conditions and being HIV negative were significantly positively associated with PCS, and low poverty, low psychological distress and being HIV positive were positively significantly associated with MCS. CONCLUSION: TB and HIV weaken patients’ physical functioning and impair their quality of life. It is imperative that TB control programmes at public health clinics design strategies to improve the quality of health of TB and HIV co-infected patients.